2021
DOI: 10.3390/cancers13246225
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Marker Immunofluorescent Staining and PD-L1 Detection on Circulating Tumour Cells from Ovarian Cancer Patients

Abstract: Detection of ovarian cancer (OC) circulating tumour cells (CTCs) is primarily based on targeting epithelial markers, thus failing to detect mesenchymal tumour cells. More importantly, the immune checkpoint inhibitor marker PD-L1 has not been demonstrated on CTCs from OC patients. An antibody staining protocol was developed and tested using SKOV-3 and OVCA432 OC cell lines. We targeted epithelial (cytokeratin (CK) and EpCAM), mesenchymal (vimentin), and OC-specific (PAX8) markers for detection of CTCs, and CD45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 65 publications
(85 reference statements)
3
17
0
Order By: Relevance
“…Reinforcing trends were seen for the association of PD-L1 activity with pEMT signature one ( Figure 1 H). Thus, this pan-cancer meta-analysis highlights that the prominent mode of association in these pairwise comparisons is that PD-L1 activity correlates positively with a partial mesenchymal nature, reminiscent of recent experimental reports [ 18 , 22 , 45 ].…”
Section: Resultssupporting
confidence: 65%
“…Reinforcing trends were seen for the association of PD-L1 activity with pEMT signature one ( Figure 1 H). Thus, this pan-cancer meta-analysis highlights that the prominent mode of association in these pairwise comparisons is that PD-L1 activity correlates positively with a partial mesenchymal nature, reminiscent of recent experimental reports [ 18 , 22 , 45 ].…”
Section: Resultssupporting
confidence: 65%
“…Reinforcing trends were seen for association of PD-L1 activity with pEMT signature one ( Fig 1H ). Thus, this pan-cancer meta-analysis highlights that the prominent mode of association in these pairwise comparisons is that PD-L1 activity correlates positively with a partial mesenchymal nature, reminiscent of recent experimental reports [19,23,47].…”
Section: Resultssupporting
confidence: 65%
“…But due to the expression of vimentin in circulating endothelial cells (CECs), CD31 was used as exclusion marker, similar to other studies 19 , 20 . We previously noted putative CTCs expressing CK/EpCAM as well as CD31 positive 18 , presenting as pseudoendothelial phenotype. Recently putative tumorigenic CECs with aneuploidy have been reported from OC 21 and lung cancer patients 22 .…”
Section: Introductionmentioning
confidence: 91%
“…In our recent study, we identified heterogeneous CTCs in ovarian cancer (OC) patients using a multi-marker immunostaining method for the detection of both epithelial and mesenchymal CTCs 18 . Mesenchymal CTCs were identified as vimentin positive cells.…”
Section: Introductionmentioning
confidence: 99%